PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN PENDAPATAN DAERAH PROVINSI KALIMANTAN BARAT - B2041142007, HADINATA SAPUTRA LIM (Universitas Tanjungpura, 2019)
This research aims to analyze how work motivation and work discipline can affect employee job satisfaction in Badan Pengelola Keuangan Dan Pendapatan Daerah Provinsi Kalimantan Barat. This study uses a descriptive research form that is used to measure the value of independent and dependent independent variables. The analysis model used in this study is a multiple regression analysis model. The techniques used are classical assumption test, validity and reliability test, and hypothesis testing. The results showed that the variables of work motivation and work discipline simultaneously had apositive and significant effect on job satisfaction. Partially, work motivation has a positive and significant effect while work discipline has a positive but not significant effect on job satisfaction.Â Keywords : Work Motivation, Work Discipline, Job Satisfaction